2021
DOI: 10.4049/jimmunol.2001386
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Unique Hepatitis C Virus–Specific Public CD8+ T Cell Clonotypes during Acute Infection and Reinfection

Abstract: Hepatitis C virus (HCV) infection resolves spontaneously in ~25% of acutely infected humans where viral clearance is mediated primarily by virus-specific CD8 + T cells. Previous cross-sectional analysis of the CD8 + TCR repertoire targeting two immunodominant HCV epitopes reported widespread use of public TCRs shared by different subjects, irrespective of infection outcome. However, little is known about the evolution of the public TCR repertoire during acute HCV and whether crossreactivity to other Ags can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, we have previously observed that, in viral infections, 50 , 53 , 54 , 55 effective T cell responses against immunodominant epitopes typically involve large clusters of TCRs with closely related sequences. Indeed, large clusters of structurally similar TCRs are present among hepatitis C virus (HCV) tetramer-positive T cells from an HCV-infected patient who spontaneously resolved their infection 56 ( Figure S5 A). Tetramer-positive TCRs from patient SJ1, on the other hand, form no clusters at all.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we have previously observed that, in viral infections, 50 , 53 , 54 , 55 effective T cell responses against immunodominant epitopes typically involve large clusters of TCRs with closely related sequences. Indeed, large clusters of structurally similar TCRs are present among hepatitis C virus (HCV) tetramer-positive T cells from an HCV-infected patient who spontaneously resolved their infection 56 ( Figure S5 A). Tetramer-positive TCRs from patient SJ1, on the other hand, form no clusters at all.…”
Section: Resultsmentioning
confidence: 99%
“… 44 http://allelefrequencies.net/hla.asp Human reference genome GRCh38 Genome Reference Consortium https://www.ncbi.nlm.nih.gov/assembly/GCF_000001405.26/ Cell Ranger human reference, GRCh38 (Ensembl 84) 10x Genomics https://support.10xgenomics.com/single-cell-gene-expression/software/release-notes/build Cell Ranger human reference, GRCh38 (Ensembl 93) 10x Genomics https://support.10xgenomics.com/single-cell-gene-expression/software/release-notes/build Cell Ranger human V(D)J reference vdj_IMGT_human 10x Genomics N/A Cell Ranger human V(D)J reference vdj_IMGT_human-None 10x Genomics N/A Cell Ranger human V(D)J reference vdj_GRCh38_alts_ensembl-3.1.0-3.1.0 10x Genomics N/A Single-chain TCR repertoire data from HCV-infected patient SR5 Mazouz et al. 56 immuneACCESS: Mazouz_Shoukry_2021 https://clients.adaptivebiotech.com/pub/mazouz-2021-ji ( https://doi.org/10.21417/SM2021JI ) Single-chain TCR repertoire data from SARS-CoV-2-infected donor M Minervina et al. 57 Zenodo: 4065547 https://zenodo.org/record/4065547 Single-chain TCR repertoire data from SARS-CoV-2-vaccinated donors 01a, 04, 20, 22 Mudd et al.…”
Section: Methodsmentioning
confidence: 99%
“…We observed a concurrent increase in HCV-specific B and T cell responses at Early acute at the transcriptomic and functional levels. Although, in our study the concurrent impact of both immune responses on the infecting viral sequence is not known, our laboratory has previously shown that spontaneous resolution of HCV reinfections was associated with an expansion of polyfunctional clonotypes recruited from preexisting memory pools [ 6 8 ]. In addition, Kinchen et al demonstrated that the capacity of nAbs to induce an immune pressure leading to mutations within the CD81 binding site of the E2 glycoprotein, eventually resulting in a loss of viral fitness [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous resolution of an HCV reinfection has been associated with a shorter duration and magnitude of viremia, a broadened cellular immune response and, in 60% of cases, generation of cross-reactive antibodies [ 5 ]. We have demonstrated that the expansion of polyfunctional memory CD4 + and CD8 + T cells as well as that of a more focused HCV-specific CD8 + T-cell receptor repertoire comprised of public clonotypes correlated with protective immunity [ 6 8 ]. Yet, deeper insights into what constitutes a potent protective immune response in real life settings is crucial for the development of a prophylactic HCV vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this assay has been used in 27 infectious diseases studies for SARS-CoV-2 [ 31 ], Hepatitis B and C [ 32 ], Mycobacterium tuberculosis [ 33 ], etc., and in 5 vaccine efficacy studies for SARS-CoV-2 [ 18 ], influenza [ 17 ], glioma [ 34 ], etc.…”
Section: Discussionmentioning
confidence: 99%